FINANCING RISK MANAGEMENT ANALYSIS ON BMT LATANSA GONTOR PONOROGO - Astuti, Rahma Yudi (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2020)
The development of Baitul Maal Wa Tamwil (BMT) is often hampered by problems such as weak member participation, weak oversight and poor risk management, these problems are identified potential risks. Therefore BMT must implement risk management correctly. The problem in this study is how the application of risk management in BMT La Tansa Gontor and how to overcome problematic financing. The purpose of this study is to analyze how the application of risk management in BMT La Tansa Gontor, and to analyze how the application of risk management in overcoming problem financing. This type of research is field research, where data acquisition from interviews with Finance and Accounting Managers at BMT La Tansa. This research is also supported by library research which aims to collect data, documents and other references related to risk management data for financing at BMT La Tansa. The results of this study, La Tansa BMT has implemented risk management properly and correctly, namely by conducting risk identification, risk measurement, risk monitoring, risk management information systems and risk control. In this way it is proven to minimize the risk of financing. Keywords: BMT La-Tansa Gontor, Risk Management, Financing